Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Masterina Adyatama Sentosa: The Influence of Motivation and Work Environment on Employee Performance at Pt Masterina Adyatama Sentosa - Oktavia Lutfi Nuraini; Iwan Asmadi (CV Warnak Johanna Nusantara, 2026)
Motivation and Work Environment are factors that affect Employee Performance. This research was conducted at PT Masterina Adyatama Sentosa. The company has a total of 36 employees, and the sample size used for this study consists of all 36. The purpose of this study is to analyze the influence of Motivation and Work Environment on Employee Performance at PT Masterina Adyatama Sentosa.This study uses a quantitative approach with survey techniques. Data was collected through the distribution of questionnaires to all employees of PT Masterina Adyatama Sentosa. The independent variables studied are Motivation and Work Environment, while the dependent variable is Employee Performance. Data analysis was performed using multiple linear regression tests to determine the effect of each variable on employee performance. The research results partially indicate that Motivation (X1) has a positive and significant effect on Employee Performance (Y) at PT Masterina Adyatama Sentosa, with a t-value of 3.472. Likewise, Work Environment (X2) also has a positive and significant effect on Employee Performance (Y) at PT Masterina Adyatama Sentosa, with a t-value of 3.418. Simultaneously, Motivation (X1) and Work Environment (X2) have a positive and significant effect on Employee Performance (Y) at PT Masterina Adyatama Sentosa, with an F-value of 7.2.